Students' interest and tendencies in using printed and electronic dictionaries in learning Arabic at Sunan Ampel University Surabaya - Taufiq, Mirwan Akhmad (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2026)
The development of technology has impacted the way students access learning resources, including the use of dictionaries as a primary tool for understanding Arabic vocabulary. This study aims to identify students' interests and preferences in using printed and electronic dictionaries to learn Arabic at Sunan Ampel University, Surabaya. This study relied on a descriptive quantitative approach using a survey method. The sample consisted of 26 students from the Department of Arabic Language and Literature and the Department of Arabic Language Education. Data was collected through an online questionnaire (G-Form) and interviews with professors in both departments. The study concluded that most students prefer electronic dictionaries because they are more practical, quicker to access, and compatible with today's digital learning style. However, some students still insist on using printed dictionaries for specific purposes that are considered more in-depth and beneficial. Several students are unaware of how to find a word in a printed dictionary, having initially relied on electronic dictionaries. These results also indicate a shift in the learning culture among Arabic language students and provide a basis for lecturers and educational institutions to adjust their learning methods and provide learning resources relevant to the needs of the digital generation.